2021
DOI: 10.1186/s12301-021-00208-z
|View full text |Cite
|
Sign up to set email alerts
|

Early outcome findings of treatment for transperitoneal laparoscopy-assisted pyeloplasty

Abstract: Background We retrospectively analyzed the initial results of laparoscopic pyeloplasty, among pediatric patients undergoing the procedure by transperitoneal access. Methods We retrospectively reviewed the medical records of patients who were operated with transperitoneal laparoscopy-assisted pyeloplasty at our institution between 2015 and 2020. Results The mean age of the 51 patients (M/F = 36/15) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Four studies agreed that APD could potentially predict the success of pyeloplasty. 18 , 19 , 26 , 29 A higher preoperative APD was associated with a higher probability of surgery failure. 15 , 18 Despite the presence of studies supporting the effect of APD, 3 studies found that APD had no significant effect on the outcomes of pyeloplasty.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Four studies agreed that APD could potentially predict the success of pyeloplasty. 18 , 19 , 26 , 29 A higher preoperative APD was associated with a higher probability of surgery failure. 15 , 18 Despite the presence of studies supporting the effect of APD, 3 studies found that APD had no significant effect on the outcomes of pyeloplasty.…”
Section: Resultsmentioning
confidence: 94%
“…This result is more interesting because more studies have shown no difference between the recovery of renal function based on age at diagnosis (pre and postnatal). 19 - 21 Salem et al 22 showed that the overall likelihood of reduced or improved preoperative DRF becoming reduced or improved in the postoperative period is not affected by age. All studies that explored the correlation between gender and results of pyeloplasty found that no association exists between the 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations